Sistema de informação geográfica para auxílio à análise e ao planejamento de rotas de viaturas policiais - Cotrim, Daniel Souza (2008)
The population growth in large urban areas is generally followed by an increase of criminal activities. Thus, the task of public safety organizations to inhibit police occurrences through the surveillance of large areas has become more and more complex. A resource still used in attempt to inhibit some kinds of police occurrences is the ostensible police work with vehicles. Vehicles are suitable for preventive police work and for a quick response for on going police occurrences. The simple execution of patrols with vehicles, however, does not guarantee the effectiveness of such resource. One of the major problems of planning patrols with vehicles to fight criminality is to identify critical periods of time and places to visit. The good planning is the one that guarantees that police vehicles will be at the right time at the right place. In this context, this work proposes a Geographical Information System to help the analysis and planning of police car patrols. The proposed tool aims at helping criminal analysts in their tasks of analyzing patrols quality planning new patrols schedules in order to allow the rational usage of police vehicles and to enhance the quality of the ostensible police work.